(untitled) (Security Dialogues, 2024)
Since 2015 the migrant crisis has affected on a global level regions and started off the worst refugee crisis since the establishment of European Union. While some countries were set to help and provide support to migrants and refugees, others turned to setting up fences, in order to stop illegal entries to their countries. Different approaches were in place depending on the state policy of the country, which majorly focused on strenghtening border control. Along with strictier border controls, the market of smuggling migrants arise and even COVID19 did not impacted the movement of migrants in a broader extent. The smuggling of migrants according to Global Initiative market assesment facilitated milllions of euros, only in 2020, while it differed a set of typology of smugglers. Smugglers use current migration, as well as political situation triggered with corruption, to make their ‘bussines’ flourish. This paper provides insights in how migration and organized crime are linked, in the sense of smuggling of migrants, and presents the market of smuggling in Bosnia and Herzegovina.